Transversalidad y valores: una propuesta metodológica para incorporarlos en los programas de estudio de ciencias y biología - Enrique Bogantes-Vílchez; Luciana Delgado-Conejo; Sandry Jiménez-Arias; María Elena Murillo-Arias; Graciela Rojas-Chaves; Geovanny Rojas-Miranda; Adriana Zúñiga-Meléndez; Silvia Morales-Herrera; Evelyn Porras (Revista Electrónica Educare)
Gender mainstreaming and values are tools that allow for social change; they are essential elements in an individual's education. When dealing whit aspects of society and values, this theory provides the teacher whit the possibility of experiencing social reality from a more human, supportive, and tolerant point of view. For this reason, the incorporation of these elements in the course outline is essential.